1999
DOI: 10.1002/(sici)1097-4598(199902)22:2<208::aid-mus8>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on exercise-induced muscle damage and interleukin 6 production

Abstract: To address the question of whether the increased plasma concentration of interleukin 6 (IL‐6) following strenuous muscular work could be related to exercise‐induced muscle damage, 5 moderately active male volunteers underwent two isokinetic exercise sessions in the eccentric mode, separated by a period of 3 weeks during which the subjects underwent five training sessions. Before training, exercise was followed by severe muscle pain (delayed‐onset muscle soreness; DOMS), and by significant increases in plasma I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 26 publications
8
69
0
3
Order By: Relevance
“…Indeed, a previous study has shown reduced pro-inflammatory cytokines (IL-6), and increased anti-inflammatory cytokines (IL-10) in the 12 hours following a repeated bout of muscle damage evoked by downhill running (Smith et al 2007), although this finding is not supported by studies that have used different models of muscle damage (e.g. isokinetic knee extensor exercise (Croisier et al 1999;Willoughby et al 2003)). We were therefore interested in whether the hypothesised reduction in heat strain could be accounted for by an altered circulating inflammatory response following EIMD.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, a previous study has shown reduced pro-inflammatory cytokines (IL-6), and increased anti-inflammatory cytokines (IL-10) in the 12 hours following a repeated bout of muscle damage evoked by downhill running (Smith et al 2007), although this finding is not supported by studies that have used different models of muscle damage (e.g. isokinetic knee extensor exercise (Croisier et al 1999;Willoughby et al 2003)). We were therefore interested in whether the hypothesised reduction in heat strain could be accounted for by an altered circulating inflammatory response following EIMD.…”
Section: Discussionmentioning
confidence: 97%
“…13,14 In addition, a recent communication has failed to find an association between increases in IL-6 and muscle damage. 28 The latter study showed that training reduced the increase in CK in response to a bout of exercise, whereas the increase in IL-6 was not influenced by a training effect. It is most likely that the huge and immediate increase in IL-6 in response to long-duration exercise is independent of muscle damage, whereas muscle damage as such is followed by repair mechanisms, including invasion of macrophages into the muscle, leading to IL-6 production.…”
Section: Exercise-induced Muscle Damage and Cytokinesmentioning
confidence: 99%
“…up-regulated by physical activity, both at the mRNA and the protein level, which is indeed responsible for the increases in the levels of systemic IL-6 concentration after exercise in rodents and human subjects [3][4][5][6]. Importantly, IL-6 was shown to have positive effects on skeletal muscle glucose disposal [7,8], and accumulating evidence demonstrated that some of the beneficial effects of exercise might be mediated by exercise factors including IL-6 [9].…”
mentioning
confidence: 99%